A polarizing plate manufacturing process and a polarizing plate having a hardened low-reflective protective layer

CN123010168APending Publication Date: 2026-10-30KUNSHAN ZHIQIMEI MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611244441.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]本发明的目的在于克服现有大尺寸偏光板在制备过程中难以兼顾外表面硬度及低反射性能、宽幅PVA偏光子制程稳定性以及多层膜材贴合稳定性的问题

Benefits of technology

本发明通过在PET基材表面依次形成HC涂层和LR涂层,并将所得HCLR-PET光学膜作为PVA偏光子的上侧保护膜,使偏光板获得由PET基材、硬化层和低反射层共同构成的外侧保护结构;同时,通过依次对PVA膜进行膨润、染色、延伸和水切处理,并将HCLR-PET光学膜、PVA偏光子和COP补偿膜通过UV胶进行三层贴合,使PVA偏光子的宽幅制备与后续膜层复合形成连续配合的制程。由此能够在满足大尺寸偏光板制备要求的基础上,兼顾偏光板外表面的耐刮擦及低反射性能,并提高宽幅膜材制备和多层贴合过程的稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123010168A_ABST
    Figure CN123010168A_ABST
Patent Text Reader

Abstract

The application discloses a polarizing plate process with a hardened low-reflection protective layer and a polarizing plate in the technical field of polarizing plates, and comprises the following steps: performing preliminary treatment on a PET base material, sequentially forming an HC coating and an LR coating on one side of the PET base material and performing UV curing to obtain an HCLR-PET optical film; sequentially performing swelling, dyeing, stretching and water cutting treatment on a PVA film to obtain a PVA polarizer; taking the HCLR-PET optical film as an upper protective film of the PVA polarizer, taking a COP compensation film as a lower compensation layer, and performing three-layer lamination and UV curing through UV glue; then, a release film is laminated with the COP compensation film through pressure-sensitive glue, and protective film treatment is performed to obtain the polarizing plate. The application can take into account the hardening and low-reflection performance of the outer surface of the polarizing plate, improve the stability of the preparation and multi-layer film lamination process of a wide PVA film, and is suitable for the preparation of a polarizing plate for a large-size liquid crystal display panel.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polarizer manufacturing process with a hardened low-reflection protective layer and to a polarizer plate, belonging to the field of polarizer technology. Background Technology

[0002] Polarizing plates are crucial optical components in liquid crystal displays (LCDs) used to achieve selective transmission of polarized light. They typically consist of PVA polarizers, protective or compensating films on either side of the PVA polarizers, pressure-sensitive adhesive layers, and release films. As LCD products, including televisions and commercial displays, trend towards larger sizes, the effective width of polarizing plates is continuously increasing, placing higher demands on their optical performance, surface scratch resistance, low reflectivity, and wide-width manufacturing process stability. Especially for ultra-large display panels of 86 inches and above, even 116 inches, polarizing plates must maintain high transmittance and polarization while also meeting the requirements for wide cutting and subsequent lamination.

[0003] Existing polarizing plates typically use TAC film as a protective film for PVA polarizers. However, TAC material is highly hydrophilic and has a relatively high moisture permeability, making it susceptible to moisture damage in high-temperature and high-humidity environments, which further affects the optical performance of PVA polarizers. Furthermore, large-size display products have a larger exposed surface area during transportation, assembly, cleaning, and use. When the outer surface hardness of the polarizing plate is insufficient or its reflectivity is high, scratches, abrasions, ambient light reflection, and glare are easily caused.

[0004] On the other hand, during the swelling, dyeing, stretching and water cutting processes, the width of wide-width PVA membranes is easily affected by factors such as tank temperature, tension, torque, stretching ratio and machine speed. Under wide-width production conditions, phenomena such as membrane width fluctuation, uneven local stretching and even membrane cracking are likely to occur. Summary of the Invention

[0005] The purpose of this invention is to overcome the problems of existing large-size polarizing plates in the manufacturing process, which make it difficult to balance the surface hardness and low reflectivity, the stability of wide-width PVA polarizing process, and the stability of multilayer film bonding.

[0006] To solve the above-mentioned technical problems, the present invention is implemented using the following technical solution: Firstly, a polarizer manufacturing process with a hardened low-reflection protective layer is provided, including the following steps: The PET substrate is pretreated, and HC coating, pre-drying and LR coating are sequentially performed on one side of the PET substrate, followed by UV curing to obtain an HCLR-PET optical film. The HCLR-PET optical film includes a PET substrate, an HC coating disposed on one side of the PET substrate, and an LR coating disposed on the outer side of the HC coating. PVA film was subjected to swelling treatment, dyeing treatment, stretching treatment and water cutting treatment in sequence to obtain PVA polarizers; The HCLR-PET optical film is used as the upper protective film for PVA polarizers, and the COP compensation film is used as the lower compensation layer for PVA polarizers. UV adhesive is applied between the HCLR-PET optical film and the PVA polarizer, and between the PVA polarizer and the COP compensation film. The three layers are then bonded together using a composite roller and UV cured to obtain an HCLR-PET / PVA / COP composite film. Pressure-sensitive adhesive is coated on the release agent side of the release film. After drying, the release film is bonded to the COP compensation film side of the HCLR-PET / PVA / COP composite film. The bonded film is then subjected to a secondary protective film treatment to obtain a polarizing plate.

[0007] Furthermore, the PET substrate is an optical-grade biaxially oriented polyethylene terephthalate film with a thickness of 40μm to 125μm, a light transmittance of not less than 88%, and a haze of not more than 1.5%. The thickness of the HC coating after curing is 2μm to 10μm, and the thickness of the LR coating after curing is 80nm to 160nm.

[0008] Furthermore, the HC coating liquid of the HC coating includes acrylate oligomers, multifunctional acrylate crosslinking monomers, inorganic nano-hardening particles, photoinitiators, leveling agents, adhesion promoters, and organic solvents. The acrylate oligomer is present in amounts of 20 to 60 parts by weight; The multifunctional acrylate crosslinking monomer is 10-45 parts by weight; The inorganic nano-hardening particles are 10-45 parts by weight; The photoinitiator is 1 to 8 parts by weight; The leveling agent is present in the form of 0.05 to 1.5 parts by weight; The adhesion promoter is 0.1 to 3 parts by weight; The solid content of the HC coating liquid is 20% to 60%.

[0009] Furthermore, the LR coating liquid of the LR coating includes fluorinated acrylate resin and / or siloxane modified acrylate resin, hollow silica particles, multifunctional acrylate crosslinking agent, photoinitiator, leveling agent and organic solvent. The fluorinated acrylate resin and / or siloxane-modified acrylate resin are in the range of 20 to 70 parts by weight. Hollow silica comprises 20 to 70 parts by weight; The multifunctional acrylate crosslinking agent is 5 to 30 parts by weight; The photoinitiator is 0.5 to 6 parts by weight; The leveling agent is 0.05 to 1 part by weight; The solid content of the LR coating liquid is 0.5% to 10%.

[0010] Furthermore, the PVA film has a saponification degree of not less than 98 mol%, and a thickness of 20 μm to 80 μm; The temperature of the tank for the swelling treatment is 20℃~30℃; The staining treatment uses a staining solution comprising iodine, potassium iodide and water; The iodine concentration is 0.01wt% to 0.5wt%, the potassium iodide concentration is 0.1wt% to 5wt%, and the temperature of the dyeing tank is 20℃ to 40℃.

[0011] Furthermore, during the swelling process: the tension at the corresponding station is controlled between 300N and 700N, and the torque is controlled between 2N and 18N; During the dyeing process: the tension at the corresponding workstation is controlled at 600N to 1000N, and the torque is controlled at 2N to 10N; During the stretching process, the tension at the corresponding station is controlled between 600N and 1000N, and the torque is controlled between 0N and 5N. During the water cutting process, the tension at the corresponding station is controlled between 300N and 700N, and the torque is controlled between 15N and 30N. The PVA film has an elongation ratio of 1.0 to 4.0 times, and the elongation speed is 10 m / min to 40 m / min.

[0012] Furthermore, the UV adhesive is a solvent-free or low-solvent acrylate UV-curable adhesive; comprising polyurethane acrylate oligomers, acrylate reactive diluents, hydrophilic modifying monomers, photoinitiators, silane coupling agents, and leveling agents; The thickness of the cured UV adhesive layer is 0.5μm to 8μm.

[0013] In a second aspect, a polarizing plate with a hardened low-reflection protective layer is provided, manufactured using the polarizing plate manufacturing process with a hardened low-reflection protective layer as described in the first aspect, and further includes: From the observation side to the liquid crystal cell side, the layers are sequentially HCLR-PET optical film, first UV adhesive layer, PVA polarizer, second UV adhesive layer, COP compensation film, pressure-sensitive adhesive layer and release film. The HCLR-PET optical film includes a PET substrate, an HC coating disposed on the surface of the PET substrate facing the observation side, and an LR coating disposed on the surface of the HC coating facing the observation side. The first UV adhesive layer is disposed between the HCLR-PET optical film and the PVA polarizer, the second UV adhesive layer is disposed between the PVA polarizer and the COP compensation film, and the pressure-sensitive adhesive layer is disposed between the COP compensation film and the release film.

[0014] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: This invention achieves a protective outer structure for the polarizing plate by sequentially forming an HC coating and an LR coating on the surface of a PET substrate, and using the resulting HCLR-PET optical film as the upper protective film for the PVA polarizer. This protective structure comprises the PET substrate, a hardened layer, and a low-reflection layer. Simultaneously, by sequentially swelling, dyeing, stretching, and water-cutting the PVA film, and then bonding the HCLR-PET optical film, PVA polarizer, and COP compensation film together using UV adhesive, a continuous process is created between the wide-width fabrication of the PVA polarizer and subsequent film layer lamination. This process satisfies the requirements for large-size polarizing plate fabrication while also ensuring scratch resistance and low reflectivity on the outer surface of the polarizing plate, and improves the stability of wide-width film fabrication and multi-layer lamination. Attached Figure Description

[0015] Figure 1 The diagram shown is a structural diagram of the HCLR-PET optical film with a hardened low-reflection protective layer in the polarizer manufacturing process provided by the present invention. Figure 2 The diagram shows the production process flow chart of the HCLR-PET optical film with a hardened low-reflection protective layer provided by the present invention. Figure 3 The image shows the HCLR-PET type polarizer lamination process with a hardened low-reflection protective layer provided by the present invention. Figure 4 The diagram shows a flowchart of the polarizer manufacturing process with a hardened low-reflection protective layer provided by the present invention. Detailed Implementation

[0016] The present invention will now be described in further detail with reference to specific embodiments and the accompanying drawings. Unless otherwise specified, the experimental methods described in this invention are all conventional methods; the materials used are all commercially available. Example 1:

[0017] This embodiment provides a polarizer manufacturing process with a hardened low-reflection protective layer.

[0018] like Figure 1 , Figure 2 and Figure 4As shown, HCLR-PET optical film is first prepared. Optical-grade biaxially oriented polyethylene terephthalate film is selected as the PET substrate. The thickness of the PET substrate can be 40μm to 125μm, with a light transmittance of not less than 88% and a haze of not more than 1.5%. For the preparation of the 116-inch polarizing plate, the PET substrate uses a master roll suitable for 2.6m wide-width production, with allowance reserved for edge material required for subsequent slitting and cutting.

[0019] The PET substrate undergoes initial treatment; specifically, after unwinding the PET substrate, surface dust removal is performed, and the side surface to be coated with the HC coating is subjected to surface activation treatment. The surface activation treatment may employ at least one of corona treatment, plasma treatment, ultraviolet ozone treatment, or primer treatment to improve the adhesion between the PET substrate and the subsequent HC coating.

[0020] In one specific embodiment, an optical-grade PET substrate with a thickness of 75 μm is selected, and one side surface of the PET substrate is subjected to corona treatment so that the surface dyn value after treatment is not less than 38 dyn / cm.

[0021] After initial treatment, HC coating is applied to the side of the PET substrate that has been surface activated. The HC coating is a UV-curable organic-inorganic composite hardening layer. The HC coating liquid includes acrylate oligomers, multifunctional acrylate crosslinking monomers, inorganic nano-hardening particles, photoinitiators, leveling agents, adhesion promoters and organic solvents.

[0022] The acrylate oligomers can be selected from one or more of polyurethane acrylates, epoxy acrylates, polyester acrylates, and silicone-modified acrylates; the multifunctional acrylate crosslinking monomers can be selected from one or more of trimethylolpropane triacrylate, pentaerythritol triacrylate, dipentaerythritol hexaacrylate, and 1,6-hexanediol diacrylate; the inorganic nano-hardening particles can be selected from one or more of surface-modified nano-silica, nano-alumina, and nano-zirconia, and the particle size of the inorganic nano-hardening particles can be 5 nm to 100 nm, preferably 10 nm to 50 nm.

[0023] Based on 100 parts by weight of solids in the HC coating solution, the composition includes 20–60 parts by weight of acrylate oligomers, 10–45 parts by weight of multifunctional acrylate crosslinking monomers, 10–45 parts by weight of inorganic nano-curing particles, 1–8 parts by weight of photoinitiator, 0.05–1.5 parts by weight of leveling agent, and 0.1–3 parts by weight of adhesion promoter. The solids content of the HC coating solution is controlled at 20%–60%, and the viscosity can be controlled at 5 mPa·s–80 mPa·s to adapt to microgravure coating, slot coating, or gravure coating.

[0024] In this embodiment, an HC coating solution is prepared using polyurethane acrylate oligomer, dipentaerythritol hexaacrylate, surface-modified nano-silica, photoinitiator, leveling agent, and organic solvent. The organic solvent is a mixed solvent composed of ethyl acetate and methyl ethyl ketone. The solid content of the HC coating solution is controlled at approximately 35%. The HC coating solution is applied to the pre-treated surface of a PET substrate using a microgravure coating method. After pre-drying at 60°C–90°C, it is UV cured to form an HC coating with a thickness of approximately 4 μm. Depending on the actual product requirements, the thickness of the cured HC coating can be controlled between 2 μm and 10 μm, preferably between 3 μm and 6 μm.

[0025] An LR coating is formed on the outer surface of the HC coating. The LR coating is a low-refractive-index UV-curable layer. The LR coating liquid includes a low-refractive-index resin, hollow silica particles and / or low-refractive-index nanoparticles, a multifunctional acrylate crosslinking agent, a photoinitiator, a leveling agent, and an organic solvent. The low-refractive-index resin can be a fluorinated acrylate resin or a siloxane-modified acrylate resin.

[0026] Based on 100 parts by weight of solids in the LR coating liquid, the following components are included: 20-70 parts by weight of fluorine-containing or silicon-containing low-refractive-index resin; 20-70 parts by weight of hollow silica or low-refractive-index nanoparticles; 5-30 parts by weight of multifunctional acrylate crosslinking agent; 0.5-6 parts by weight of photoinitiator; and 0.05-1 parts by weight of leveling agent. The solid content of the LR coating liquid is controlled at 0.5%-10%, preferably at 1%-5%. The particle size of the hollow silica particles can be 20nm-150nm, preferably 40nm-100nm.

[0027] In this embodiment, an LR coating solution was prepared by mixing fluorinated acrylate resin, hollow silica particles, a multifunctional acrylate crosslinking agent, a photoinitiator, and a mixed solvent of isopropanol / propylene glycol methyl ether. The solid content of the LR coating solution was controlled at approximately 2.5%. The LR coating solution was applied to the outer surface of the HC coating, dried at low temperature, and then UV cured to form an LR coating with a thickness of approximately 110 nm.

[0028] The thickness of the cured LR coating can be controlled between 80nm and 160nm, preferably between 90nm and 130nm, and its refractive index after curing can be controlled between 1.20 and 1.45, preferably between 1.25 and 1.38. By controlling the thickness of the LR coating within the above range, the thickness of the LR coating is close to the quarter-wavelength anti-reflection condition of the visible light center band, thereby reducing the reflection of ambient light on the observation side of the polarizing plate.

[0029] The HC coating and LR coating can be formed by first forming the HC coating and then semi-curing or fully curing it, then applying the LR coating and finally UV curing it; or the HC coating can be pre-dried after application to achieve a surface dry state, then the LR coating can be applied and segmented UV curing can be performed; before applying the LR coating, the surface temperature of the base film can be controlled between 20℃ and 35℃.

[0030] After the above processing, an HCLR-PET optical film is obtained. The HCLR-PET optical film consists of a PET substrate, an HC coating, and an LR coating from the inside out. The HC coating is used to improve the surface hardness and scratch resistance of the observation side surface of the polarizing plate, and the LR coating is used to reduce the reflection of ambient light on the observation side surface of the polarizing plate.

[0031] For the preparation of PVA polarizers, a PVA film with a saponification degree of not less than 98 mol% and a thickness of 20 μm to 80 μm is selected as the polarizer base film, preferably with a thickness of 30 μm to 60 μm. The PVA film undergoes swelling treatment, dyeing treatment, stretching treatment, and water cutting treatment in sequence. The swelling treatment is used to allow the PVA film to absorb water and swell, providing a uniform film state for subsequent dyeing and stretching. The swelling tank uses deionized water or an aqueous solution containing additives, and the tank temperature is controlled at 20℃ to 30℃, preferably 20℃ to 25℃. During the swelling treatment, the tension at the corresponding station is controlled at 300N to 700N, and the torque is controlled at 2N to 18N.

[0032] The dyeing solution for the dyeing process includes iodine, potassium iodide, and water. The concentration of iodine is controlled at 0.01wt% to 0.5wt%, the concentration of potassium iodide is controlled at 0.1wt% to 5wt%, and the temperature of the dyeing tank is controlled at 20℃ to 40℃. During the dyeing process, the tension at the corresponding workstation is controlled at 600N to 1000N, and the torque is controlled at 2N to 10N.

[0033] After dyeing, the PVA film undergoes a stretching treatment to orient the PVA molecular chains and their adsorbed iodine complexes along the stretching direction. The stretching bath solution may include boric acid, potassium iodide, and water. Boric acid is used for crosslinking and dimensional stabilization of the PVA segments. During the stretching treatment, the tension at the corresponding station is controlled between 600N and 1000N, and the torque is controlled between 0N and 5N. The stretching ratio of the PVA film is controlled between 1.0 and 4.0 times, and the stretching machine speed is controlled between 10m / min and 40m / min.

[0034] After the stretching process, the PVA film undergoes a water-cutting process to remove residual chemicals and free water from its surface and to stabilize the film before proceeding to the subsequent lamination process. During the water-cutting process, the tension at the corresponding station is controlled between 300N and 700N, and the torque is controlled between 15N and 30N.

[0035] like Figure 3As shown, after the PVA polarizer is fabricated, the HCLR-PET optical film is used as the upper protective film for the PVA polarizer, and the COP compensation film is used as the lower compensation layer for the PVA polarizer. The bonding side of the HCLR-PET optical film can be pre-treated with corona discharge, plasma, or primer, and the bonding side of the COP compensation film can also be surface activated.

[0036] A first UV adhesive is placed between the HCLR-PET optical film and the PVA polarizer, and a second UV adhesive is placed between the PVA polarizer and the COP compensation film. The UV adhesive used is a solvent-free or low-solvent acrylate UV-curable adhesive, including polyurethane acrylate oligomers, acrylate reactive diluents, hydrophilic modified monomers, photoinitiators, silane coupling agents, and leveling agents.

[0037] To balance the adhesion performance between the hydrophilic surface of PVA and the relatively hydrophobic surface of PET and COP, the hydrophilic modified monomer can be a reactive monomer containing hydroxyl, carboxyl, amide or epoxy groups, and can be combined with silane coupling agents or isocyanate modified components to improve interlayer adhesion.

[0038] Based on 100 parts by weight of UV adhesive solids, the polyurethane acrylate oligomer can be 30-70 parts by weight, the acrylate reactive diluent can be 20-60 parts by weight, the hydrophilic modifying monomer can be 2-20 parts by weight, the photoinitiator can be 1-8 parts by weight, the silane coupling agent can be 0.1-5 parts by weight, and the leveling agent can be 0.05-1 parts by weight.

[0039] The HCLR-PET optical film, PVA polarizer, and COP compensation film are fed into the composite roller via unwinding rollers. The first and second UV adhesives can be coated on both sides of the PVA polarizer, or on the respective bonding sides of the HCLR-PET optical film and the COP compensation film. After being bonded by the composite roller, the three layers enter the UV curing section, where the first and second UV adhesives are cured to form the HCLR-PET / PVA / COP composite film. The cured thickness of the first and second UV adhesive layers can be 0.5 μm to 8 μm, preferably 1 μm to 5 μm.

[0040] During the three-layer lamination process, the lamination tension is adjusted according to the thickness, width, and warpage of each membrane layer to control the warpage of the laminated body within -5mm to 20mm. For 2.6m wide membrane materials, zoned tension or multi-segment tension compensation methods can be used to control the membrane tension at different locations to reduce S-shaped bending, edge warpage, and center wrinkles caused by unilateral tension deviation.

[0041] UV curing can be performed using mercury lamps, metal halide lamps, or LED-UV light sources. The UV wavelength can be 365nm, 385nm, 395nm, or 405nm, and the irradiation dose can be controlled between 200mJ / cm² and 2000mJ / cm², preferably between 500mJ / cm² and 1200mJ / cm². The temperature of the UV curing section is controlled between 30℃ and 70℃ to reduce the thermal shrinkage of PVA polarizers and the phase change of the COP compensation film caused by the curing process.

[0042] After the three layers are laminated, pressure-sensitive adhesive is applied to the release agent side of the release film. The pressure-sensitive adhesive can be an optical grade acrylic pressure-sensitive adhesive, including an acrylic copolymer, a crosslinking agent, a tackifying resin, an antistatic agent, a UV absorber, and a solvent. The dry film thickness of the pressure-sensitive adhesive can be controlled between 10 μm and 35 μm, preferably between 15 μm and 25 μm. After the pressure-sensitive adhesive is coated, it is dried in a segmented oven at 80℃ to 120℃, for example, by using a segmented heating method of 80℃, 100℃, and 120℃. Then, the pressure-sensitive adhesive side of the release film is laminated to the COP compensation film side of the HCLR-PET / PVA / COP composite film.

[0043] The release film can be made of PET, with a silicone oil release layer on its surface, and the release force can be controlled between 5gf / 25mm and 50gf / 25mm.

[0044] After the release film is applied, a secondary protective film treatment is performed on the film material. Specifically, a temporary protective film can be applied to the outer surface of the HCLR-PET optical film on the observation side at the RK line, and the warpage of the film material is finally adjusted. The protective film is used to reduce scratches and contamination on the LR coating surface during subsequent winding, slitting, cutting, transportation and assembly.

[0045] The processed film material is then wound into a finished roll. The winding tension is tapered according to the roll diameter to reduce indentations and unevenness at the ends of the roll. The finished roll undergoes a slitting process to remove edge material and form a master roll width suitable for subsequent cutting. It is then cut by RTS to form a polarizing plate of the required size. The polarizing plate thus formed includes, from the observation side to the liquid crystal cell side, an HCLR-PET optical film, a first UV adhesive layer, a PVA polarizer, a second UV adhesive layer, a COP compensation film, a pressure-sensitive adhesive layer, and a release film. Among them, the HCLR-PET optical film includes, from the observation side towards the PVA polarizer, an LR coating, an HC coating, and a PET substrate. Example 2:

[0046] This embodiment further explains the low-reflection structure of the HCLR-PET optical film based on the manufacturing process described in Embodiment 1.

[0047] The PET substrate is made of optical-grade biaxially oriented PET film with a thickness of about 75μm, and one side of it is corona treated to make the surface dyn value not less than 38dyn / cm.

[0048] The HC coating solution uses polyurethane acrylate oligomer as the main resin, dipentaerythritol hexaacrylate as a multifunctional acrylate crosslinking monomer, and adds surface-modified nano silica as inorganic nano-hardening particles. At the same time, photoinitiators, leveling agents and corresponding additives are added, and a mixture of ethyl acetate and methyl ethyl ketone is used as an organic solvent to control the solid content of the HC coating solution at about 35%.

[0049] The HC coating solution was applied to the surface of a PET substrate using a microgravure method. After pre-drying at 60℃~90℃, it was UV cured to form an HC coating with a thickness of approximately 4μm. After forming the HC coating, an LR coating solution was prepared using fluorinated acrylate resin, hollow silica particles, multifunctional acrylate crosslinking agent, photoinitiator, and a mixed solvent of isopropanol / propylene glycol methyl ether, with a solid content controlled at approximately 2.5%. The LR coating solution was applied to the outer surface of the HC coating, dried at low temperature, and then UV cured to form an LR coating with a thickness of approximately 110nm.

[0050] The resulting HCLR-PET optical film consists of an LR coating, an HC coating, and a PET substrate, arranged from the outside in.

[0051] In other embodiments, the LR coating thickness can be set to 80 nm, 110 nm, or 150 nm, respectively. When the LR coating thickness is in the range of 90 nm to 130 nm, it can better approach the quarter-wavelength antireflection condition of the visible light center band, thereby obtaining a stable antireflection effect. When the LR coating is too thin, the antireflection cancellation effect is relatively insufficient; when the LR coating is too thick, it may cause hue shift, increased haze, or decreased surface abrasion resistance.

[0052] Therefore, by layering HC coating and LR coating, a hardened low-reflection surface structure is formed on the outside of the PET substrate. The HC coating mainly provides surface hardening and scratch resistance, while the LR coating mainly reduces ambient light reflection. Together, they form the HCLR protective structure on the observation side of the polarizing plate.

[0053] Example 3: This embodiment, based on Embodiment 1, further explains the wide-area PVA wet zone treatment and subsequent bonding applicable to 116-inch polarizing plates.

[0054] Wide-width PVA film is selected as the polarizer base film, and the PVA film is sequentially introduced into the swelling tank, dyeing tank, stretching tank and water cutting tank.

[0055] The temperature of the swelling tank is controlled at 20℃~30℃, the tension of the corresponding station in the swelling tank is controlled at 300N~700N, and the torque is controlled at 2N~18N; the tension of the corresponding station in the dyeing tank is controlled at 600N~1000N, and the torque is controlled at 2N~10N; the tension of the corresponding station in the stretching tank is controlled at 600N~1000N, and the torque is controlled at 0N~5N; the tension of the corresponding station in the water-cutting tank is controlled at 300N~700N, and the torque is controlled at 15N~30N.

[0056] The PVA film elongation ratio is controlled between 1.0 and 4.0 times, and the elongation processing machine speed is controlled between 10 m / min and 40 m / min. In an implementation suitable for 2.6 m wide-width production, by reducing the swelling tank temperature, adjusting the wet zone solution conditions, and reducing the overall production speed, the excessive lateral expansion of the PVA film during the swelling stage is reduced. The overall machine speed can be controlled between 20 m / min and 25 m / min, reducing the film width before and after swelling by approximately 100 mm to 120 mm, and further reducing the film width after exiting the wet zone by approximately 30 mm to 40 mm, thereby stabilizing the PVA film width at approximately 2600 mm before entering the three-layer lamination process.

[0057] The PVA polarizer, the HCLR-PET optical film prepared in Example 2, and the COP compensation film were unwound separately. UV adhesive was applied to both sides of the PVA polarizer, and the HCLR-PET / PVA / COP three-layer composite was performed using a composite roller. During the lamination process, the tension of the three layers of film was adjusted to control the warpage of the laminated body within -5mm to 20mm.

[0058] The composite film enters the UV curing section, where the first UV adhesive located between the HCLR-PET optical film and the PVA polarizer, and the second UV adhesive located between the PVA polarizer and the COP compensation film are cured, thus obtaining the HCLR-PET / PVA / COP composite film.

[0059] Subsequently, optical-grade acrylic pressure-sensitive adhesive is coated on the release agent side of the release film. After drying in a segmented oven, the release film is bonded to the COP compensation film side of the HCLR-PET / PVA / COP composite film. Then, the protective film is bonded to the outer surface of the HCLR-PET optical film along the RK line, and the film warpage is finally adjusted.

[0060] After the above processing is completed, the product is wound up, slit and RTS cut to obtain a 116-inch polarizing plate, and then inspected for appearance, optical performance, size and warpage.

[0061] The resulting polarizing plate has a single-cell transmittance of over 43.5%, a polarization degree of over 99.995%, a haze of less than 1%, an outer surface hardness of over 500g / 3H for HCLR-PET, a side surface reflectance of less than 1.5%, and can undergo 1000 hours of RA weather resistance testing.

[0062] The above description is merely a preferred embodiment of the present invention, but is not intended to limit the implementation of the present invention. Those skilled in the art should understand that any modifications, equivalent substitutions, and improvements made based on the present invention without departing from the inventive concept of the present invention are within the scope of protection of the present invention.

Claims

1. A process for manufacturing a polarizing plate with a hardened low-reflection protective layer, characterized in that, Includes the following steps: The PET substrate is pretreated, and HC coating, pre-drying and LR coating are sequentially performed on one side of the PET substrate, followed by UV curing to obtain an HCLR-PET optical film. The HCLR-PET optical film includes a PET substrate, an HC coating disposed on one side of the PET substrate, and an LR coating disposed on the outer side of the HC coating. PVA film was subjected to swelling treatment, dyeing treatment, stretching treatment and water cutting treatment in sequence to obtain PVA polarizers; The HCLR-PET optical film is used as the upper protective film for PVA polarizers, and the COP compensation film is used as the lower compensation layer for PVA polarizers. UV adhesive is applied between the HCLR-PET optical film and the PVA polarizer, and between the PVA polarizer and the COP compensation film. The three layers are then bonded together using a composite roller and UV cured to obtain an HCLR-PET / PVA / COP composite film. Pressure-sensitive adhesive is coated on the release agent side of the release film. After drying, the release film is bonded to the COP compensation film side of the HCLR-PET / PVA / COP composite film. The bonded film is then subjected to a secondary protective film treatment to obtain a polarizing plate.

2. The polarizer manufacturing process with a hardened low-reflection protective layer according to claim 1, characterized in that, The PET substrate is an optical-grade biaxially oriented polyethylene terephthalate film with a thickness of 40μm to 125μm, a light transmittance of not less than 88%, and a haze of not more than 1.5%. The thickness of the HC coating after curing is 2μm to 10μm, and the thickness of the LR coating after curing is 80nm to 160nm.

3. The polarizer manufacturing process with a hardened low-reflection protective layer according to claim 1, characterized in that, The HC coating liquid comprises acrylate oligomers, multifunctional acrylate crosslinking monomers, inorganic nano-hardening particles, photoinitiators, leveling agents, adhesion promoters, and organic solvents. The acrylate oligomer is present in amounts of 20 to 60 parts by weight; The multifunctional acrylate crosslinking monomer is 10-45 parts by weight; The inorganic nano-hardening particles are 10-45 parts by weight; The photoinitiator is 1 to 8 parts by weight; The leveling agent is present in the form of 0.05 to 1.5 parts by weight; The adhesion promoter is 0.1 to 3 parts by weight; The solid content of the HC coating liquid is 20% to 60%.

4. The polarizer manufacturing process with a hardened low-reflection protective layer according to claim 1, characterized in that, The LR coating liquid comprises fluorinated acrylate resin and / or siloxane-modified acrylate resin, hollow silica particles, multifunctional acrylate crosslinking agent, photoinitiator, leveling agent and organic solvent. The fluorinated acrylate resin and / or siloxane-modified acrylate resin are in the range of 20 to 70 parts by weight. Hollow silica comprises 20 to 70 parts by weight; The multifunctional acrylate crosslinking agent is 5 to 30 parts by weight; The photoinitiator is 0.5 to 6 parts by weight; The leveling agent is 0.05 to 1 part by weight; The solid content of the LR coating liquid is 0.5% to 10%.

5. The polarizer manufacturing process with a hardened low-reflection protective layer according to claim 1, characterized in that, The degree of saponification of the PVA film is not less than 98 mol%, and the thickness is 20 μm to 80 μm; The temperature of the tank for the swelling treatment is 20℃~30℃; The staining treatment uses a staining solution comprising iodine, potassium iodide and water; The iodine concentration is 0.01wt% to 0.5wt%, the potassium iodide concentration is 0.1wt% to 5wt%, and the temperature of the dyeing tank is 20℃ to 40℃.

6. The polarizer manufacturing process with a hardened low-reflection protective layer according to claim 5, characterized in that, During the swelling process: the tension at the corresponding station is controlled between 300N and 700N, and the torque is controlled between 2N and 18N; During the dyeing process: the tension at the corresponding workstation is controlled at 600N to 1000N, and the torque is controlled at 2N to 10N; During the stretching process, the tension at the corresponding station is controlled between 600N and 1000N, and the torque is controlled between 0N and 5N. During the water cutting process, the tension at the corresponding station is controlled between 300N and 700N, and the torque is controlled between 15N and 30N. The PVA film has an elongation ratio of 1.0 to 4.0 times, and the elongation speed is 10 m / min to 40 m / min.

7. The polarizer manufacturing process with a hardened low-reflection protective layer according to claim 1, characterized in that, The UV adhesive is a solvent-free or low-solvent acrylate UV-curable adhesive; it includes polyurethane acrylate oligomers, acrylate reactive diluents, hydrophilic modified monomers, photoinitiators, silane coupling agents, and leveling agents. The thickness of the cured UV adhesive layer is 0.5μm to 8μm.

8. A polarizing plate with a hardened low-reflection protective layer, characterized in that, It is manufactured using the polarizer fabrication process with a hardened low-reflection protective layer as described in any one of claims 1-7, and further includes: From the observation side to the liquid crystal cell side, the layers are sequentially HCLR-PET optical film, first UV adhesive layer, PVA polarizer, second UV adhesive layer, COP compensation film, pressure-sensitive adhesive layer and release film. The HCLR-PET optical film includes a PET substrate, an HC coating disposed on the surface of the PET substrate facing the observation side, and an LR coating disposed on the surface of the HC coating facing the observation side. The first UV adhesive layer is disposed between the HCLR-PET optical film and the PVA polarizer, the second UV adhesive layer is disposed between the PVA polarizer and the COP compensation film, and the pressure-sensitive adhesive layer is disposed between the COP compensation film and the release film.